Coupling Secondary Ion Mass Spectrometry and Atom Probe Tomography for Atomic Diffusion and Segregation Measurements. (30th January 2019) - Portavoce, Alain; Hoummada, Khalid; Chow, Lee
Abstract: For a long time, secondary ion mass spectrometry (SIMS) was the only technique allowing impurity concentrations below 1 at% to be precisely measured in a sample with a depth resolution of few nanometers. For example, SIMS is the classical technique used in microelectronics to study dopant distribution in semiconductors and became, after radiotracers were forsaken, the principal tool used for atomic transport characterization (diffusion coefficient measurements). Due to the lack of other equivalent techniques, sometimes SIMS could be used erroneously, especially when the analyzed solute atoms formed clusters, or for interfacial concentration measurements (segregation coefficient measurements) for example. Today, concentration profiles measured by atom probe tomography (APT) can be compared to SIMS profiles and allow the accuracy of SIMS measurements to be better evaluated. However, APT measurements can also carry artifacts and limitations that can be investigated by SIMS. After a summary of SIMS and APT measurement advantages and disadvantages, the complementarity of these two techniques is discussed, particularly in the case of experiments aiming to measure diffusion and segregation coefficients.